Political Uncertainty and Household Stock Market Participation - Agarwal, Vikas; Aslan, Hadiye; Huang, Lixin; Ren, Honglin (Journal of Financial and Quantitative Analysis, 2022)
Abstract Using microlevel panel data and a difference-in-differences identification strategy, we study the effect of political uncertainty on household stock market participation. We find that households significantly reduce their participation and reallocate funds to safer assets during periods of increased political uncertainty prior to gubernatorial elections. The decline in participation is related to households’ response to elevated asset risk and their incentive to hedge increased labor income risk. In situations where uncertainty remains high after elections, pre-election reduction in participation is only partially reversed.